Correction: Lopresti, M. et al. The Crystal Structure of Calcium Sebacate by X-ray Powder Diffraction Data. Crystals 2023, 13, 261 - Mattia Lopresti; Marco Milanesio; Luca Palin (Crystals, 2024)
In the original publication [...]